Economia solidária: um estudo sobre as incubadoras públicas municipais - Ferreira, Fernanda Machado (2018)
As an alternative for the generation of work and income of excluded people in the formal labor market, there are the enterprises of Solidary Economy. Among the entities in support of these enterprises are incubators. In Brazil, what is the greatest impact of incubator support in this line are those created by universities, however, there is an embryonic work to create incubators of socioeconomic enterprises by municipal governments. Therefore, because it is still a recent phenomenon and has few reports in the literature that deal with the theme, this work consisted of the effort to favor the performance of Municipal Public Incubators with proposals for innovation and intervention that reflect on society. For this reason, the objective of this research was to analyze the role of the Municipal Public Incubators in the ambit of strengthening the Solidarity Economy and to propose a methodology model of the same. The research uses the research procedure multicasos study, with qualitative and quantitative approach with interest in the application. For the development of the model, a survey of the national production of studies on methodology of incubation of enterprises of solidarity economy was carried out, taking as reference the practices adopted by university incubators. For the analysis of the Municipal Public Incubators, the data were collected through documentary research and the interview. The interviews had three distinct locus, which were: Social Incubator of the Federal University of Goias, municipal public incubators and cooperatives of collectors of recyclable materials of the cities of Anápolis, Aparecida de Goiânia, Hidrolândia, Nerópolis and Trindade. With the collected data, to analyze the data, we performed content analysis and application of the mathematical method of Data Envelopment Analysis (DEA). The study provided an opportunity to understand the public policies of solidarity economy, to understand the impact of municipal public incubators, to analyze the role of university incubators in the development of these local incubators, and to develop a model of incubation methodology to strengthen and strengthen actions incubators. The results demonstrate the fundamental role of incubators to boost socioeconomic ventures and the need for advances in incubators to perform the entire incubation process, playing their role of training with autonomy and expanding their field of action. Among the products of the study is the developed model that allows a multiplier effect for the generation of work and income for the population excluded from the formal labor market, because from relevant social results, city halls may be motivated to create their municipal incubator of enterprises of solidarity economy and, thus, increase the number of incubators and incubated enterprises.